LANGUAGE NORMS IN THE ASPECT OF TYPOLOGICAL COMPARISON AND INTER-LANGUAGE CONTRASTS (BY THE MATERIAL OF THE RUSSIAN AND UZBEK LANGUAGES) - Komilova Sevara Usmonjon kizi (Academia Science Repository, 2023)
The article highlights the most contrasting with the Uzbek language aspects of Russian morphemics, word formation and morphology, which present particular difficulties for Uzbek students in mastering the norms of the Russian language.